A longitudinal analysis of a work inclusion model for psychiatric patients in the Mental Health Departments of the city of Milan. (December 2022) - Ferrara, Luca; Varinelli, Alberto; Caricasole, Valentina; Dragoni, Chiara; Mazzardis, Sonia; Quarenghi, Andrea; Rubelli, Paola; Fusi, Antonio; Percudani, Mauro; Cisima, Michele; Mencacci, Claudio; Maranesi, Teodoro; et al.
Background: Work functioning impairment is a key diagnostic and transnosographic criterion for psychiatric disorders in both DSM-5 and ICD-11. Occupational inclusion is a fundamental aspect of the care path for patients attending the territorial services provided by the Italian Mental Health and Addiction Departments (DSMDs). Since 2009, the Regional Innovative Programme (PIR) TR106, promoted by the Fatebenefratelli-Sacco hospital of Milan, Italy, in collaboration with six other metropolitan DSMDs, was created to promote integration for people suffering from mental health problems in the city of Milan. Method: Here we present the results of a retrospective epidemiologic analysis on 2, 142 interventions on 1, 066 patients, conducted between 2012 and 2019. Results: Most of the interventions were conducted with people with psychotic disorders (39%), followed by personality disorders (25.2%) and affective disorders (22.2%). The age range of 25 to 54 years represented 91.5% of the whole sample, mainly in the 35 to 44 years range (36.4%). Significant age group-related changes in interventions were observed in the observation period, with a reduction in the interventions provided to subjects of the 35 to 44 age group, and an increase in the 25 to 34 age group. Conclusions: PIR TR106 provided the most accurate assessment and data collection so far for the city of Milan. Our data characterised psychiatric groups in order to develop specific treatment plans and work inclusion interventions.